Hubungan Antara Dukungan Keluarga Dengan Body Image Pada Wanita Dewasa Madya Di Kelurahan Tangsi Kecamatan Binjai Kota - Elia Devita Perangin-Angin; Andy Chandra (Universitas Medan Area, 2022)
This study aims to determine the relationship between family support and body image of middle adult women in Tangsi Village, Binjai City District. The sample in this study were 75 middle adult women. The hypothesis proposed in this study is that there is a positive relationship between family support and body image. This study was measured based on the Likert scale method using aspects of family support according to Kaplan (in Friedman, 2003), namely: emotional support, instrumental support, informational support, and assessment support. Furthermore, the body image scale is based on aspects according to (Cash Pruzinsky, 2002) namely: evaluation of appearance, appearance orientation, satisfaction with body parts, anxiety about being fat, categorization of body parts. Based on the results of the analysis using the Product Moment correlation analysis method. The results showed that there was a positive relationship between family support and body image, where rxy = 0.679 with a significant p = 0.000 0.050. This means that the proposed hypothesis is accepted. The coefficient of determinant (r2) of 0.460 indicates that family support contributes to body image by 46%. Based on the results of the calculation of the hypothetical and empirical mean values, it can be concluded that family support is low with a hypothetical mean value of 55 and an empirical mean of 43.39. Furthermore, it can be concluded that body image is classified as negative with a hypothetical value of 85 and an empirical value of 68.00.